Left ventricular hypertrophy, diastolic dysfunction and right ventricular load predict outcome in moderate aortic stenosis - Stöbe, Stephan; Kandels, Joscha; Metze, Michael; Tayal, Bhupendar; Laufs, Ulrich; Hagendorff, Andreas (Frontiers in Cardiovascular Medicine, 2023)
Aims: Predictors of progression of moderate aortic valve stenosis (AS) are incompletely under-stood. The objective of this study was to evaluate the prognostic value of left ventricular hyper-trophy (LVH), diastolic dysfunction, and right ventricular (RV) load in moderate AS. Methods and Results: moderate AS was defined by aortic valve area (AVA), peak transval-vular velocity (Vmax) or mean pressure gradient (PGmean). 131 Patients were divided into two groups according to the number of pathophysiological changes (LVH, diastolic dysfunction with increased LV filling pressures and/or RV load): < 2 (group 1);  2 (group 2). The primary outcome was survival without aortic valve replacement (AVR). After follow-up of 30 months, the reduction of AVA (-0.06 ± 0.16cm2 vs -0.24 ± 0.19cm2, P < 0.001), the increase of PGmean (2.89 ± 6.35mmHg vs 6.29 ± 7.13mmHg, P < 0.001) and the decrease of the global longitudinal strain (0.8 ± 2.56% vs 1.57 ± 3.42%, P < 0.001) from base-line to follow-up were significantly more pronounced in group 2. Survival without AVR was 82% (group 1) and 56% (group 2) (HR 3.94 [1.74-8.94], P < 0.001). Survival without AVR or progression of AS was 77% (group 1) and 46% (group 2) (HR 3.80 [1.84-7.86], P < 0.001). The presence of  2 pathophysiological changes predicted outcome whereas age, comorbidities, LDL-cholesterol did not. Conclusion: The presence of  2 pathophysiological changes is a strong predictor of outcome in moderate AS and may be useful for risk stratification, particularly for scheduling follow-up time intervals and deciding the timing of AVR.